Mildronate effects on cognitive function in elderly patients with arterial hypertension - S. V. Nedogoda; M. E. Statsenko; S. V. Turkina; I. A. Tyshchenko; L. V. Poletaeva; V. V. Tsoma; A. A. Ledyaeva; E. N. Chumachok; O. L. Bykova (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To assess the effects of the “interval” (3 months of treatment, followed by treatment-free 3 months) and “persistent” (52 weeks) therapy with Mildronate (500 mg/d) in elderly patients with arterial hypertension (AH) and cognitive dysfunction. Material and methods. In total, 1800 elderly patients with AH and mild to moderate cognitive dysfunction were randomised into 3 groups. Group I (“interval” treatment) included 60 patients (28 men and 32 women; mean age 69,13±1,09 years), who received Mildronate 500 mg once a day in the morning for 3 months, then had a treatment-free period of 3 months, followed by 3 months of therapy and 3 months of no therapy. Group II (“persistent” treatment) included 60 patients (20 men and 40 women; mean age 73,25±2,19 years), who received Mildronate 500 mg once a day in the morning for 12 months. Group III (controls) included 60 patients (16 men and 44 women; mean age 67,75±2,05 years), who were administered only standard antihypertensive treatment. The groups were comparable by age, gender, concomitant pathology, and blood pressure levels. To assess the cognitive status at Weeks 4, 12, 26, and 52, all participants underwent neuro-psychological testing (Mini-Mental State Examination (MMSE), Schulte test, Reiten test, Wechsler test, speech, memory (memorising 10 words), and counting test). Results. In elderly patients with AH, both regimens of Mildronate treatment were significantly associated with preserved cognitive and mnestic functions, which was manifested in increased mean scores of MMSE and its time domain. However, the “interval” Mildronate treatment was more beneficial than the “persistent” therapy, as the former was also linked to a significant improvement in attention and speech MMSE domain, reduction in the time of memorising 10 words and performing Reiten test, improvement in delayed memorisation, and increased mean score in Wechsler test. Conclusion. Additional treatment with Mildronate (500 mg/d), as both “interval” and “persistent” therapy, was associated with preserved cognitive and mnestic functions in elderly AH patients.